Use of visual analytics and durometer in risk reduction of foot problems in diabetes - Mishra V.; Rautela A.; Manjunatha B.; Samuel C.; Sharma S.K.; Mishra A. (My University, 2025)
Foot Problems are a leading cause of hospitalization for patients having diabetes in India. Fifteen percent of all patients of diabetes develop foot ulcer during their life time. The cost of treatment increases significantly in people with diabetes and treatment may result in lower extremities amputations (LEAs). The Visual Analytics, Correction in Foot Care Hardness can help in early detection of people at risk of Foot Ulcer. The paper finds out the average hardness of male and female foot wears in Indian population. With help of visual analytics paper tries to find out the prevalence of people at risk of foot ulcer in diabetes. The paper also explores whether the risk of foot ulcer is significantly higher for a specific gender. The methods used for analysis is t-test and Chi-Square test. © Springer India 2016.